(untitled) (Research, Society and Development, 2021)
Museums are important spaces that stimulate reflection, creativity and help in the process of knowledge construction and teaching-learning for teachers, students and the community. The objective of this work was to carry out a state of the art of scientific articles from 2011 to 2020, in relevant journals, with the theme of science and biology in Brazilian museums, through a bibliographic documentary analysis. The journals analyzed have qualis A1 and A2 in the area of Teaching and Education and they were chosen based on the Platform Sucupira of the Coordination for the Improvement of Higher Education Personnel - Capes. Forty-six articles were found and from their analysis, it was observed that the main theme found was museums with areas of natural/general sciences, with the largest number of works in the Museum of Astronomy and Related Sciences and Espaço Ciência Viva Museum, being the Southeast region predominant with the states of Rio de Janeiro and São Paulo. The main target audience of the research was museum staff and elementary school teachers, and qualitative analysis was the most used approach. The results found reveal few works developed about science/biology in museums in Brazil, but that the existing works demonstrate diversification regarding museum spaces, methodological tools for obtaining data and target audience, and reinforce the importance of museums as places of democratization of science.